An alternative food neophobia scale (FNS-A) to quantify responses to new foods. (October 2022) - De Kock, Henriëtte L.; Nkhabutlane, Pulane; Kobue-Lekalake, Rosemary I.; Kriek, Jeanine; Steyn, Annelize; Clarissa, Van Heerden; Purdon, Lucy; Kruger, Christi; Kinnear, Marise; Taljaard-Swart, Hanri; Tuorila, Hely
Graphical abstract: Highlights: An alternative Food Neophobia Scale (FNS-A) was developed and validated. The FNS-A has four positive and four negative statements regarding new foods. The FNS-A instrument can be experienced here bit.ly/FNS-A. Abstract: An alternative Food Neophobia Scale (FNS-A) was developed in three studies to measure food neophobia (reluctance to eat and avoidance of trying new foods). In Study 1, the original food neophobia scale, FNS (Pliner, & Hobden, 1992), was first critically examined leading to modifications in five and omission of two statements. Furthermore, eight positive and eight negative statements were elicited and introduced along with eight original or modified FNS statements to 575 respondents in South Africa, Lesotho, and Botswana. Study 2 (n = 1010) was used to confirm the factorial structure of the scale, and Study 3 (n = 141) was used to test the reliability of FNS-A through test–retest data. The structure of the scale was analyzed using exploratory (Study 1 and 2) and confirmatory (Study 2) factor analysis, eventually leading to four positive and four negative statements regarding new foods, loaded on two factors labelled approach and avoidance. Test-retest reliability at a 2 weeks' time interval as well as convergent and divergent validity measured against other scales was good (Study 3). In all three studies, predictive validity was evaluated against willingness to try or expected liking ratings of unfamiliar or novel food names or food concept descriptions. This evaluation showed satisfactory performance. FNS-A is a promising tool for the quantification of individual responses to unfamiliar or novel foods, but further studies in other populations and contexts are needed to confirm the applicability.